Research on Digital Transformation of Urban Emergency Management System from the Perspective of Innovation Ecology Theory - Xiao, Chenchen (International Journal of Social Sciences and Public Administration, 2025)
Urbanization intensifies safety challenges and strains traditional emergency management systems, hindering effective crisis response. This study explores digital transformation as a solution to enhance response efficacy, constructing a novel 'ecology-mechanism-objective' analytical framework. It analyzes technology-driven, system-driven, and strategy-driven innovation models, examining their interplay with policy, technological, cultural, and economic factors. Based on this analysis, the study proposes tailored implementation pathways for advancing China's urban emergency management capabilities in the digital era, addressing specific contextual needs.